Health Behavioural Status of Gender Differences in Older People - Bhatta, Deepak Raj (Kutumbha vani, 2024)
Aging is a universal phenomenon with no single definition, varying across cultures, time, and space. The health and well-being of older adults are significantly influenced by their behaviors, which often vary by gender. These differences can impact physical health, mental health, and overall quality of life. This study explores the health behavioral status of older adults, focusing on gender differences and how these disparities affect their health indicators. Such changes impact the health status of older people, making it harder for them to manage daily tasks and access healthcare. Conducted in Dhangadhi Sub-Metropolitan City, Kailali District, Nepal, this study aims to understand the socio-economic and health status of older people. Objectives include examining gender differences in health behavior among the elderly in this region. Gender differences in health behaviors among older adults significantly impact their health. Women engage more in preventive behaviors and seek healthcare services, while men engage in riskier behaviors and underutilize services. Understanding these differences is crucial for developing effective, gender-specific interventions to improve older adults’ health and well-being. Gender differences were significant, with males showing a higher percentage of better health compared to females, and females showing slightly higher rates of bad health compared to males. Vision problems were prevalent, with a majority reporting no issues, some reporting minor problems, and a smaller portion having normal vision. Significant vision problems were reported by a notable fraction of respondents. Respiratory diseases were more prevalent among males than females, indicating a significant gender association. Gout or knee pain was more common in females than males, also showing a significant gender difference. Diabetes affected a larger portion of males compared to females, indicating a significant gender association. Blood pressure issues were slightly more prevalent in males compared to females, showing a significant gender association. Emotional health conditions such as grief, depression, and sadness showed significant gender differences, with females more likely to experience these issues.